The past, present, and the future of community corrections in South Korea: focusing on probation - Lee, Claire Seungeun (The Routledge handbook on global community corrections, 2024)
The probation system in South Korea is a prominent form of community corrections. The Crime Prevention Policy Bureau (CPPB), operating under the Ministry of Justice, holds the primary authority for overseeing probation services in the country. The CPPB is responsible for a broad range of tasks, including the supervision of probation services, management of community service orders, intervention orders, and pre-sentence investigations. This chapter provides an overview of different types of Korean community corrections and delineates a historical trajectory of probation in South Korea. This chapter also discusses organization and supervision practice, major related laws, and the future prospect of community corrections in South Korea.